Hericium erinaceus polysaccharides improve eggshell quality by improving uterine health and modulating uterine microbiota in aged hens - Lianchi Wu; Zhaoying Hu; Yujie Lv; Chaoyue Ge; Xinyu Luo; Shenao Zhan; Weichen Huang; Xinyu Shen; Dongyou Yu; Bing Liu (Animal Nutrition)
Hericium erinaceus polysaccharide (HEP) is widely regarded as a potential food additive because of its rich nutritional value. This study aimed to explore the effect of HEP on the eggshell quality of aged laying hens and to reveal the mechanisms with particular emphasis on the alterations of uterine microbiota and health. A total of 360 Jingbai laying hens at 58 weeks old were randomly allocated into 4 groups, with 6 replicates per treatment and 15 birds per replicate. The hens were fed basal diets supplemented with 0, 250, 500, or 750 mg/kg HEP for 8 weeks. The results showed that HEP supplementation enhanced eggshell quality by improving the eggshell ultrastructure, as evidenced by increased eggshell thickness and strength (P < 0.05). HEP decreased the abundance of Enterobacterales, Yersiniaceae, and Rahnella and increased the abundance of Actinobacteria in the uterus (P < 0.05). HEP inhibited the activation of the toll-like receptor 4 (TLR4)/nuclear factor kappa B (NF-κB) signaling pathway and decreased (P < 0.05) the mRNA expression of interleukin-1β (IL-1β) and tumor necrosis factor alpha (TNF-α). HEP promoted cell proliferation, as evidenced by the increased (P < 0.05) expression of proliferating cell nuclear antigen (PCNA) and Proliferation Ki-67 (Ki67), and reduced necrotic apoptosis by downregulating (P < 0.05) the mRNA expression of cysteinyl aspartate specific proteinase 3 (Caspase-3) and cysteinyl aspartate specific proteinase 9 (Caspase-9). HEP restored the physiological function of the uterus and improved eggshell biomineralization as evidenced by the increased mRNA levels of ATPase plasma membrane Ca2+ transporting 1 (ATP2B1), ATPase plasma membrane Ca2+ transporting 2 (ATP2B2), and solute carrier family 26 member 9 (SLC26A9) and decreased ovotransferrin (OVOT) expression (P < 0.05). These findings suggest that dietary HEP supplementation can improve the functional integrity of the uterus and modulate uterine microbiota. The enhanced functional integrity of the uterus facilitates the regulation of the expression of proteins involved in eggshell biomineralization, thereby ultimately improving eggshell quality through the modulation of eggshell ultrastructure.